Household Decision Making Of Women In Public Service In Nigeria - Hauwa , Daniyan-Bagudu; Mohd Khan, Shazida Jan; Roslan, Abdul-Hakim (2016)
This study examines the impact of women decision making in the household especially among the public servants in Nigeria. The study used a sample of 350 public servant women, and applied a Logistic regression model. The result shows that women decision making on family health care is positive and significant, while household repairs and constructions are negative and significantly related to household status. The study therefore recommends a sensitization program to educate men on the importance or role of women in decision making especially in the household and also for economic development.